2007
DOI: 10.1167/iovs.06-0618
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Study Design and Spectrum Bias on the Evaluation of Diagnostic Accuracy of Confocal Scanning Laser Ophthalmoscopy in Glaucoma

Abstract: Estimates of diagnostic accuracy of CSLO in glaucoma can be largely different depending on the population studied and the reference standard used to define disease. Diagnostic accuracy estimates obtained from case-control studies including well-defined groups of subjects with or without disease may not be applicable to the clinically relevant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 32 publications
2
48
0
2
Order By: Relevance
“…Such a design has been shown to inflate the actual diagnostic ability of a test. 30,31 Another limitation, in general to all studies in glaucoma is the lack of reference standard for diagnosing the disease. Our glaucoma cohort included patients with evidence of both structural changes in optic disc and correlating visual field changes.…”
Section: Discussionmentioning
confidence: 99%
“…Such a design has been shown to inflate the actual diagnostic ability of a test. 30,31 Another limitation, in general to all studies in glaucoma is the lack of reference standard for diagnosing the disease. Our glaucoma cohort included patients with evidence of both structural changes in optic disc and correlating visual field changes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, normal subjects had no suspicious findings of disease and were generally required to have normal optic discs, whereas in our study, normal subjects had optic discs with a suspicious appearance, making it more difficult for the diagnostic test to differentiate them from diseased subjects. In fact, a recent study by Medeiros et al 10 evaluating the impact of design-related bias in studies of diagnostic tests in glaucoma found that studies with a case-control design including patients with well-established disease and a separate group of normal (unsuspected) control subjects resulted in substantial overestimation of the test's performance.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis based on longitudinal follow-up can then be used as a reference standard with which the results of the imaging instruments are to be compared. 10,11 In the present study, we compared the RNFL and optic disc topographic assessment by SLP and CSLO, respectively, to detect glaucomatous damage in patients suspected of having the disease. Long-term follow-up was used to establish diagnosis in these patients and as a reference standard for comparison of results.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to rule-out the diagnosis of glaucoma completely in suspect eyes unless followed up for a reasonable period of time. Medeiros et al 39 have therefore advocated the use of progressive optic disc change over follow-up examinations as the reference standard for glaucoma. This possibility of including a few preperimetric glaucoma cases in the control cohort, affecting the comparison of diagnostic abilities between SDOCT and GDx ECC should therefore be kept in mind.…”
Section: Discussionmentioning
confidence: 99%